Proximity-Dependent Biotinylation Approaches to Explore the Dynamic Compartmentalized Proteome - Dionne, Ugo; Gingras, Anne-Claude (Frontiers in Molecular Biosciences, 2022)
In recent years, proximity-dependent biotinylation approaches, including BioID, APEX, and their derivatives, have been widely used to define the compositions of organelles and other structures in cultured cells and model organisms. The associations between specific proteins and given compartments are regulated by several post-translational modifications (PTMs); however, these effects have not been systematically investigated using proximity proteomics. Here, we discuss the progress made in this field and how proximity-dependent biotinylation strategies could elucidate the contributions of PTMs, such as phosphorylation, to the compartmentalization of proteins.